2018
DOI: 10.4103/aian.aian_421_17
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic stroke and cerebral venous thrombosis: rare neurological sequelae of chickenpox infection

Abstract: Chickenpox (varicella) is primarily a disease of childhood which occurs due to infection with varicella-zoster virus (VZV). Primary VZV infection is rare in adults due to exposure in early childhood in our country. In adults, it is associated with some serious systemic and neurological complications which can follow both primary infection and reactivation of VZV. Neurological sequelae caused by primary VZV infection are rare and include encephalitis, aseptic meningitis, myelitis, acute cerebellar ataxia, Reye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Some concerns have also been raised about cases of CVST with thrombocytopenia following COVID-19 vaccination with AstraZeneca [8]. Although not widely known, CVST associated with VZV and HZV has been reported in several case reports [9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some concerns have also been raised about cases of CVST with thrombocytopenia following COVID-19 vaccination with AstraZeneca [8]. Although not widely known, CVST associated with VZV and HZV has been reported in several case reports [9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…VZV and HZV have been linked to vasculopathy and arterial strokes and, less often, venous strokes, such as CVST and cerebral venous thrombosis (CVT) [14,20]. The mechanisms behind this association are not well understood [18].…”
Section: Discussionmentioning
confidence: 99%
“…Of the other 5 cases, 3 had mild pleocytosis and a mild increase in protein [ 19 , 23 ]; among these, only 1 confirmed the presence of the virus in the CSF by PCR. Two cases had a slight increase in protein in the CSF [ 16 , 20 ], with positive IgM in CSF in only 1 of them. These results indicate that VrCVST can occur as a complication of varicella, even without central nervous system (CNS) infection.…”
Section: Discussionmentioning
confidence: 99%
“…4 The various proposed mechanisms of these complications include direct neurological damage, immune-mediated damage and vasculopathy. 5 Isolated facial nerve paralysis is a relatively rare complication of varicella. 6 , 7 In a previous study, it was reported in 8.3% of the patients.…”
Section: Discussionmentioning
confidence: 99%